PEDAGOGICAL-PSYCHOLOGICAL METHODS IN PREVENTING FAMILY AND INTER-PERSONAL CONFLICTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the importance of the decisions taken at the state level in the prevention of violence between individuals and families and the role of pedagogical and psychological recommendations and methods in its delivery to the population. In particular, the importance of developing new methods of rehabilitation and adaptation in today's situation is listed.